2020
DOI: 10.1167/iovs.61.14.3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Adrenergic Agonists Stimulate Fluid Secretion in Lacrimal Gland Ducts

Abstract: The role of adrenergic innervation in the regulation of lacrimal gland (LG) ductal fluid secretion is unknown. The Aim of the present study was to investigate the effect of adrenergic stimulation on fluid secretion in isolated LG duct segments and to study the underlying intracellular mechanisms. METHODS. Fluid secretion of isolated mouse LG ducts was measured using videomicroscopy. Effect of various adrenergic agonists (norepinephrine, phenylephrine, and isoproterenol) on fluid secretion as well as inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Besides the apparent role of parasympathetic agonists, a substantial outcome of α-adrenergic activation on LG ductal secretion was also proven in our previous experiments. 10 To assess the role of AQP4 in the α-adrenergic stimulation-induced fluid secretion, PHE (10 µM) was applied. Although PHE induced a relevant secretory response in both WT and KO ducts, this response was significantly lower in ducts isolated from AQP4 KO LGs (WT = 274 ± 63 pl/min/mm 2 and AQP4 KO = 158 ± 53 pl/min/mm 2 , respectively, P = 0.006; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the apparent role of parasympathetic agonists, a substantial outcome of α-adrenergic activation on LG ductal secretion was also proven in our previous experiments. 10 To assess the role of AQP4 in the α-adrenergic stimulation-induced fluid secretion, PHE (10 µM) was applied. Although PHE induced a relevant secretory response in both WT and KO ducts, this response was significantly lower in ducts isolated from AQP4 KO LGs (WT = 274 ± 63 pl/min/mm 2 and AQP4 KO = 158 ± 53 pl/min/mm 2 , respectively, P = 0.006; Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 Autonomic regulation of ductal function has also been investigated. 10 These accumulating experimental results provide compelling evidence that ductal cells possess an essential, albeit species-dependent function in the formation of the final secreta of the LG. 11 …”
mentioning
confidence: 97%
“…It is clear that, through dynamic modulations of its lipid environment and associated proteins, the ER–PM contact site plays a huge regulatory role on the spatiotemporal activity of the versatile second messengers Ca 2+ and cAMP. Therefore, a better understanding of this complex regulation may also reveal unknown aspects of crucial cell functions, such as ion and fluid secretion [ 273 , 274 , 275 , 276 , 277 , 278 ]. However, as we only start to appreciate its complexity, many open questions still need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This subject has also revealed the intricacies of assessments involving the bipolar issue. In addition, it was observed that the thickness of the alpha2-AR was enhanced in the platelets patients' who had bipolar disorder [38] (2) Beta2-Adrenergic Receptors. Studies on the quantities of beta2-adrenergic receptors in peripheral cells, however, have shown inconsistent outcomes, with one finding being that depressed individuals' leukocytes have lower levels of beta-AR-stimulated AC activity [39,40,41,42].…”
Section: Studies On Peripheral Blood Cellsmentioning
confidence: 99%
“…This subject has also revealed the intricacies of assessments involving the bipolar issue. In addition, it was observed that the thickness of the alpha2-AR was enhanced in the platelets patients' who had bipolar disorder [ 38 ]…”
Section: Gpcrs and Mood Disordersmentioning
confidence: 99%